Variability of the cortisol awakening response and morning salivary oxytocin in late adolescence. (7th November 2018) - Van Dam, Jago M.; Garrett, Amy J.; Schneider, Luke A.; Buisman‐Pijlman, Femke T. A.; Short, Michelle A.; Hodyl, Nicolette A.; Edwards, Hannah K.; Goldsworthy, Mitchell R.; Pitcher, Julia B.
Abstract : Exogenously administered oxytocin interacts with the hypothalamic‐pituitary‐adrenal (HPA) axis to modulate endogenous cortisol levels, suggesting a synergistic role for these two hormones in the response to stress, cognitive performance and the development of psycho‐behavioural disorders. The cortisol awakening response (CAR) is considered a reliable measure of HPA axis function in humans. However, the CAR appears to vary considerably from day to day and may be strongly influenced by the anticipated demands of the day ahead. The level of variation intrinsic to the CAR is unclear because few studies have examined the CAR in the absence of daily environmental variation. It is not known whether oxytocin has a similar or complementary awakening response. Therefore, over three consecutive days, we examined 12 adolescents (aged 15‐17 years) in a highly‐controlled sleep laboratory. Saliva was collected on days 4‐6 of a 9‐day laboratory visit. Cortisol and oxytocin levels were determined by an enzyme‐linked immunosorbent assay from saliva sampled at 0, 15, 30 and 45 minutes, and 8 and 12 hours post‐awakening. CAR magnitude varied between days and was associated with sleep duration and pre‐awakening sleep stage. Conversely, oxytocin levels dropped dramatically in the first 15 minutes post‐awakening and were highly consistent across participants and days. Older participants had higher awakening oxytocin concentrations. Although cortisol increases and oxytocin rapidly declines upon awakening, their diurnal variation does not appear to be related at basal, peripheral levels, consistent with a previous finding that exogenously administered oxytocin only modulates cortisol under conditions of stress.